Contactless measurement of colossal magnetoresistance in La1-xSrxMnO3 using the infrared magnetorefractive effect - Marques, RFC; Abernethy, P. R.; Matthew, JAD; Paiva-Santosa, C. O.; Perazolli, L.; Jafelicci, M.; Thompson, S. M. (Elsevier B.V., 2004)
The magnetorefractive effect (MRE) has been used for the first time to study the magnetotransport properties of La1-xSrxMnO3 perovskite materials. A direct correlation between the MRE and colossal magnetoresistance was observed. Samples with x = 0-0.3 prepared using the homogeneous coprecipitation and the solid state reaction methods were studied, covering the range of insulating to metallic behaviour. The M RE probed both the magnetically induced modification of the scattering of Drude-like electrons and the magnetic dependence of a stretching vibration mode. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: CMR; magnetorefractive effect; infrared reflection spectroscopy; perovskite; lanthanum strontium-doped manganite